Spatial dynamic models with short panels: Evaluating the impact of home purchase restrictions on housing prices - HUANG, Naqun (Institutional Knowledge at Singapore Management University, 2021)
Since the 2007 housing crisis in the United States, many countries have begun implementing various macroprudential policies to curb the ongoing rise in housing prices. As there is no clear consensus in the literature on the efficacy of these interventions, understanding their short-term impacts is crucial in informing future policy designs. Adapting a new econometric technique, we examine the short-term impact of home purchase restrictions in Singapore, accounting for the short panel nature of the data and the existence of dynamic, spatial, spatiotemporal, and unit-specific effects. Using quarterly housing data over 2012Q4-2014Q2, we find that public housing prices decrease by 3%–5% in the four quarters following policy implementation, but transaction volume does not change. These effects are likely driven by a decrease in the housing demand and the inelastic housing supply in the short run. We also show that models that ignore spatial and dynamic effects can overestimate policy effects.